SIFAT FISIK DAN KIMIA PUREE JAMBU BIJI MERAH (Psidium guajava L.) DENGAN PENAMBAHAN GUM ARAB DAN GUM XANTHAN - Diana Mahfiatus Salimah; Triana Lindriati; Bambang Herry Purnomo (JURNAL AGROTEKNOLOGI, 2015)
Pink guava (Psidium guajava L.) is one of popular fruit in Indonesia. This fruit is available easily and has reasonable price, but this fruit including perishable climacteric fruit . One solution to such damage is making pink guava into refined products such as fruit puree. The aim of this study determine the effect of the use of arabic gum and xanthan gum on the physical, chemical and organoleptic characteristic of pink guava puree. This study used a completely randomized design with factorial pattern of physical and chemical properties and using a Friedman test for organoleptic properties. Organoleptic properties was done on the juice of pink guava puree. The highest quality was pink guava puree that produced by 0,3 % xanthan gum addition. The puree had mouisture content of 87.570%; 12.430% total solids; 9,8 oBrix dissolved solids; pH4,307; the acidity 0.5790 mg of citric acid / 100 g; Vitamin C 57.160 mg / 100g; the value of L (ligthness) 34,500 and a value of 16.287.Keywords: pink guava, puree, arabic gum, xanthan gum